Sports Marketing as a Tool for Creating an Image of Leading European Football Clubs - Zemła, Paulina (Marketing sportowy jako narzędzie kreowania wizerunku czołowych europejskich klubów piłkarskich, 2022)
The purpose of the article was to describe the sports marketing tools used by leading European football clubs. As the topic was complex, the paper also included a description of the most popular marketing tools in sport. The essence of the article was to present how the image was created by four selected football clubs. The analysis of the above-mentioned activities allowed the author to confirm that the sports marketing tools they use are an effective way to achieve the intended image goals. The main thesis put forward in the paper is that sports marketing is an effective tool for creating a brand image for European sports clubs. Thanks to the availability of contents in literature, internet materials and reports, the said thesis has been proven. When used correctly, sports marketing can create a positive image of a football club in many ways, mainly thanks to modern technology and the development of social media. However, a significant function is still performed by traditional forms of advertising which cannot be replaced by modern marketing. Each football club builds a promotional strategy in a different way, and therefore the topic is complex.
[w:] Ekonomia i międzynarodowe stosunki gospodarcze / pod red. Aleksandry Kuźmińskiej-Haberli. - Wrocław: Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2022, s. 37-48
Keywords: marketing; sports marketing; brand; image; advertising; football; sport; football clubs; marketing sportowy; marka; wizerunek; piłka nożna; kluby piłkarskie; reklama